Determination of Susceptibility Determination of Pattern of Fosfomycin against Drug Resistant Bacteria Obtained from Non - Urinary Clinical Samples in a Tertiary Care Hospital, South India - Ethirajulu, Premalatha; Duraipandian, Jeyakumari; Sankararaman, Kandasamy; Paul, Sony Mary; Vivekkumar, Priestly; Rathnamgiri, Sukumar (Recent Developments in Medicine and Medical Research Vol. 1, 2021)
Background: Multi drug resistance (MDR) in bacterial infections has been an ever growing problem worldwide. To combat this some of the old drugs like fosfomycin used in the past are revived. The aim of our study was to know the susceptibility of fosfomycin for the drug resistance isolates from non - urinary samples. Most of the studies showed less susceptibility of fosfomycin to Pseudomonas aeruginosa. The objectives of the study were (i) To determine the susceptibility of fosfomycin against Methicillin sensitive and Resistant Staphylococcus aureus, ESBL producing Escherichia coli, Klebsiella species and Metallo Beta Lactamase producing Pseudomonas aeruginosa isolated from the specimens other than urine and to evaluate the agreement between the two methods, disk diffusion and agar dilution methods performed as per CLSI guidelines. Methods: First isolate of each species per patient (n=250) were tested for susceptibility to fosfomycin concomitantly by the disk diffusion and agar dilution methods described by CLSI guidelines and comparison of the two methods were studied. Results: Staphylococcus aureus and ESBL E. coli were showing 100% susceptibility, Whereas ESBL producing Klebsiella species showed 88% susceptibility to fosfomycin 200 \(μ\)g/disc and 80% and 72% by agar dilution method as per CLSI and EUCAST criteria. For MBL producing Pseudomonas aeruginosa, 90% isolates were susceptible to fosfomycin 200 \(μ\)g/disc and in agar dilution (60%) (\(\le\)32 \(μ\)g/ml) were susceptible as per EUCAST criteria. Disk diffusion method showed good agreement for S. aureus and E. coli whereas moderate agreement for Klebsiella species and very poor for Pseudomonas aeruginosa. Conclusion: Fosfomycin can be considered as an alternate drug to treat infections with multi drug resistant bacteria, not only for the UTI but for systemic infections also. This is achievable with establishment of breakpoint values and zone diameter for all common isolates.